Hubungan Self-Efficacy dengan Self-Management pada Penderita Hipertensi di Poliklinik dan Rawat Inap RSUD Haji Abdoel Madjid Batoe Batanghari - Eva Yunita; Dasuki Dasuki; Ani Astuti (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
The prevalence of hypertension in the world is currently quite high, both in Africa and Southeast Asia. The only hospital that is a referral center for the Batanghari community is the Haji Abdoel Madjied Batoe Regional Hospital. cases of hypertension are also still quite common in this hospital. Hypertension that is not controlled properly will cause various impacts on sufferers such as stroke, heart disease and even death. This study aims to determine the relationship between self-efficacy and self-management in hypertension sufferers at the Polyclinic and Inpatient Unit of the Haji Abdoel Madjid Batoe Regional Hospital, Batanghari. This study is a quantitative study with a cross-sectional design. The time and place of the study were carried out on June 12, 2023-June 30, 2023 at the Haji Abdoel Madjid Batoe Regional Hospital, Batanghari. The population in this study were all hypertension patients in June 2023 at the Polyclinic and Inpatient Unit of the Haji Abdoel Madjid Batoe Regional Hospital with a total of 110 people. The sample consisted of 87 respondents. The sampling technique was accidental sampling. The results of the study showed that more than half had poor self-management (54.0%), more than half had poor self-efficacy (56.3%). There was a significant relationship between self-efficacy and self-management in hypertension patients at the Polyclinic and Inpatient of Haji Abdoel Madjid Batoe Batanghari Hospital. Nurses should provide leaflets about hypertension self-management when patients are going home so that the contents of the leaflet can be applied, become a concern and direction to control their blood pressure.